A Method for the Analysis of Free Carbenes Present after NHC‐Organocatalyzed Transformations. Issue 30 (16th August 2017) - Das, Tamal Kanti; Biju, Akkattu T.
Abstract : In N‐heterocyclic carbene (NHC) based organocatalysis, usually, the free carbene is generated in situ by treatment of the azolium salt with a base. Described herein is a method for the analysis of the NHC present in the reaction flask after the NHC‐organocatalyzed reaction. For this, the reaction mixture was treated with elemental sulfur after the reaction and the thus‐formed thiourea/thione derivative was isolated. Common NHC‐catalyzed transformations such as benzoin reactions, Stetter reactions, homoenolate annulation reactions, and reactions proceeding via the α, β‐unsaturated acylazolium intermediate have been studied. The results indicate that after the reactions, 28–84 % of the initial carbenes exist in the free form. Abstract : A systematic analysis of free N‐heterocyclic carbenes (NHCs) present in the reaction flask after NHC‐organocatalyzed reactions has been performed by treating the reaction mixture with elemental sulfur and isolating and analyzing the formed thiourea/thione derivatives.